2016
DOI: 10.1120/jacmp.v17i3.6001
|View full text |Cite
|
Sign up to set email alerts
|

A software tool to automatically assure and report daily treatment deliveries by a cobalt‐60 radiation therapy device

Abstract: The aims of this study were to develop a method for automatic and immediate verification of treatment delivery after each treatment fraction in order to detect and correct errors, and to develop a comprehensive daily report which includes delivery verification results, daily image‐guided radiation therapy (IGRT) review, and information for weekly physics reviews. After systematically analyzing the requirements for treatment delivery verification and understanding the available information from a commercial MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The ViewRay TM system (ViewRay Inc., Cleveland, OH), provides a unique combination of a magnetic resonance imaging system and a tri-Co-60 radiation therapy system [7]. The TPS of the ViewRay system is the MRIdian TM (version 4.1.1; ViewRay Inc., Cleveland, OH, USA); its dose calculation algorithm is based on the Monte Carlo simulation [7][8][9][10]. Based on previous studies that showed differences in DVHs among commercially available TPSs, the MRIdian system should also be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The ViewRay TM system (ViewRay Inc., Cleveland, OH), provides a unique combination of a magnetic resonance imaging system and a tri-Co-60 radiation therapy system [7]. The TPS of the ViewRay system is the MRIdian TM (version 4.1.1; ViewRay Inc., Cleveland, OH, USA); its dose calculation algorithm is based on the Monte Carlo simulation [7][8][9][10]. Based on previous studies that showed differences in DVHs among commercially available TPSs, the MRIdian system should also be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The software automatically generates a report comparing both original and secondary dose calculation in terms of dose-volume-histogram (DVH) parameters as well as gamma analysis. Additionally, the vendor-supplied QA tool also compares the original treatment plan to the reoptimized daily plan regarding number of segments, segment shapes and weights, and Monitor Units [6], [22], [23], [24]. After delivery, the system generates a report containing a delivery record as well as an evaluation of recorded Monitor Units and MLC leaf positions compared to the planned values.…”
Section: Treatment Planning and Deliverymentioning
confidence: 99%
“…Detailed descriptions of the initial planning process, simulation, and MRgRT treatment device, including its imaging characteristics and dedicated treatment planning system (TPS), have been previously published. 4 , 5 , 6 , 7 For this pediatric patient, simulation comprised both CT and MRI, with use of CT as the primary data set. The gross tumor volume (GTV) was defined as the preoperative visible tumor volume with modifications accounting for return of organs to their normal anatomic position after surgery.…”
Section: Treatment Planning and Deliverymentioning
confidence: 99%
“…Detailed descriptions of the initial planning process, simulation, and MRgRT treatment device, including its imaging characteristics and dedicated treatment planning system (TPS), have been previously published 4, 5, 6, 7. For this pediatric patient, simulation comprised both CT and MRI, with use of CT as the primary data set.…”
Section: Treatment Planning and Deliverymentioning
confidence: 99%